[RETRACTED] Model Pendidikan Karakter Berbasis Kearifan Lokal - Mutaqin, Enjen Zaenal; Hayati, Fitroh; Aulia, Elsa Sivia Nur (Jurnal Penelitian Agama, 2024)
This article is retracted because it has been published in another publication (Proceedings of the 3rd Asian Education Symposium (AES 2018)) in English version with the title "Character Education Model Based on Local Wisdom (An ethnographic study in Kampung Dukuh, Ciroyom, Garut Regency, West Java)" with DOI 10.2991/aes-18.2019.99